Lost in transition: labour market entry sequences of school leaves in Europe - Brzinsky-Fay, Christian (Berlin, 2006)
"Transitional labour markets (TLMs) aim at fostering individual employability over a person's life course under the conditions of flexible labour markets. For TLM policies it is therefore necessary to focus not on single transitions or points of time but on transitional periods. Such a period can contain more than one single transition and add up to an overall sequence type. In particular, the process of labour market entry is characterised by considerable insecurity and varies in duration across individual. From a European perspective, it seems inappropriate to focus on the national level. European policies for tackling youth unemployment should be complementary to certain types of transitional sequences rather than focus on a particular institutional setting. In the paper I examine sequences of school-to-work transitions in ten European countries by using explorative methods of optimal matching and cluster analysis.